2004
DOI: 10.1111/j.0021-8782.2004.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle actin and vimentin as markers of testis development in the harbour porpoise (Phocoena phocoena)

Abstract: Testicular development in the harbour porpoise Phocoena phocoena was examined using animals ( n = 192) stranded or by-caught off the coast of England, Wales and Scotland. Classification of animals according to their stage of sexual development was undertaken using gonadal morphology and the distribution of cytoskeletal proteins. Smooth muscle actin (SMA) and vimentin proved particularly useful in this respect; SMA was prominent in the myoid peritubular cells of the adult testis, and two stages of peritubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In addition, immunostaining for desmin, SMA and vimentin was already present at this stage. These findings correlate well with observations of interstitial blood vessels in the developing testes of the sheep (Steger and Wrobel, ), harbour porpoise (Holt et al., ) and bovine (Wrobel et al., ; Devkota et al., ). In the current study, Leydig cells were observed in close proximity to the interstitial blood vessels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, immunostaining for desmin, SMA and vimentin was already present at this stage. These findings correlate well with observations of interstitial blood vessels in the developing testes of the sheep (Steger and Wrobel, ), harbour porpoise (Holt et al., ) and bovine (Wrobel et al., ; Devkota et al., ). In the current study, Leydig cells were observed in close proximity to the interstitial blood vessels.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the development of strong SMA immunostaining in peritubular myoid cells coincided with the formation of elongated spermatids in the seminiferous tubules. An increase in the intensity of SMA immunostaining in relation to testicular maturation has been reported in the rat (Palombi et al., ), sheep (Steger and Wrobel, ), porpoise (Holt et al., ) and bovine (Devkota et al., ). Due to the increase in the intensity of immunostaining during development, SMA is regarded as a marker for peritubular myoid cell differentiation (Tung and Fritz, ).…”
Section: Discussionmentioning
confidence: 80%
“…Peritubular myoid cells are known to stimulate total protein production by Sertoli cells and to increase the Sertoli cell production of androgen-binding protein and transferrin. They produce a protein named P-mod-S, that has been shown to be an important regulator of Sertoli cell function in vitro (Anthony et al 1991) and they are also considered to be highly influential in modulating the effects of androgens on the seminiferous tubule, and therefore upon spermatogenesis itself (Holt et al 2004). a-SMA is mainly found in cells having contractile functions and is therefore a powerful probe in the study of smooth muscle cell differentiation in normal and pathological conditions (Skalli et al 1986;van Nassauw et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, the aSMA is regarded as a marker of terminal smooth muscle differentiation (Skalli et al 1986). In addition, aSMA has been recently shown to signal the beginning of blood-testis barrier formation rather than its completion (Holt et al 2004). Several immunohistochemical studies have also detected aSMA in the adult testis of rat (Palombi et al 1992), monkey (Schlatt et al 1993), ram , bull Abd-Elmaksoud 2005) and human (Holstein et al 1996) as well as in the epididymis of rat (Francavilla et al 1983), bull (Alkafafy 2005), and dog (Egger and Witter 2009).…”
Section: Introductionmentioning
confidence: 99%
“…4B. c) that may match to the type IV collagen, but as what we have demonstrated that the laser might be allocated on the tunica propia that content of collagen fibril network and smooth muscle actin [39] , and its thickness is approximately 2.5 µm, meanwhile the depth resolution of laser is 5µm. Consequently, intensity of those Raman bands (peak) may assign to moiety of collagen and F-actin that is somewhat higher in control than treatment group.…”
Section: Resultsmentioning
confidence: 72%